(untitled) (Indonesian Tax Justice Review, 2025)
Judicial interpretation plays a decisive role in shaping tax justice outcomes. This paper examines selected Indonesian Supreme Court decisions addressing tax avoidance and aggressive tax planning. Using doctrinal jurisprudential analysis, the study evaluates judicial reasoning, consistency, and the application of economic substance principles. The findings reveal divergent interpretations and a tendency toward formalistic reasoning, which may limit the effectiveness of anti-avoidance rules. The paper argues that inconsistent jurisprudence undermines legal certainty and weakens deterrence against aggressive tax planning. The global contribution of this study lies in demonstrating how apex court jurisprudence influences the enforcement of tax justice in developing countries. Indonesia’s Supreme Court decisions provide comparative insights for jurisdictions seeking to strengthen judicial responses to tax avoidance. The study contributes to global debates on the role of courts in advancing equitable taxation by highlighting the importance of coherent doctrine and judicial capacity.